MORAL VALUE IN THE PATRIOT MOVIE AND RELATION WITH 18th CENTURY - Ramdhan, Muhammad; Sudjatnika, Tenny; Assiddiqi, Hasbi (Universitas Islam Negeri Sunan Gunung Djati, 2022)
Movie is one of the media that has a significant impact on the dissemination of information and the transmission of messages to readers or the general public. This study aimed to discover moral value in